The Level of Dental and Oral Health Knowledge on Parents, Teachers and Students of SD Tunas Harapan Islam Medan - Yanti, Nevi; Batubara, Fitri Yunita; Octiara, Essie; Siregar, Darmayanti (Talenta Publisher, 2020)
Based on SEARO (South-East Asia Region) data in 2013, shows that around 70-95% of dental caries occurs in school-age children. This shows the importance of knowledge of dental and oral health to make efforts to prevent dental and oral diseases. The knowledge of parents and teachers has an important role in influencing children's attitudes and behavior in maintaining oral and dental hygiene. The purpose of this study was to determine the level of knowledge of parents, teachers, and students of SD Tunas Harapan Islam Medan about oral health. This study used a pretest questionnaire for initial data collection, then counseling on dental and oral health to parents and teachers and for final data collection a postest questionnaire was used. The results of the dependent T test showed that there was a difference in the average results of the questionnaire before and after counseling for parents and teachers (p = 0.0001) and students (p = 0.0001). So it can be concluded that there is an effect of doing counseling on the level of knowledge of parents, teachers and students about oral health. Counseling on oral health at SD Tunas Harapan Islam Medan can provide an understanding of the importance of maintaining oral health and of course it can be passed on to families and the surrounding environment so that the environment of SD Tunas Harapan Islam Medan can be free from dental and oral diseases.